Reduction of Chlorophyll in Cold‐Pressed Hemp (Cannabis sativa) Seed Oil by Ultrasonic Bleaching and Enhancement of Oxidative Stability. Issue 4 (8th February 2018) - Liang, Jingbang; Aachary, Ayyappan A.; Hydamaka, Arnold; Eskin, N. A. Michael; Eck, Peter; Thiyam‐Holländer, Usha
Abstract : The effects of ultrasonic bleaching on chlorophyll reduction and oxidative stability of cold‐pressed Cannabis sativa (hemp) seed oil is investigated using three different clays, Sepiolite, activated Bentonite, and an industrial clay. The chlorophyll content is significantly reduced ( p  < 0.05) from 56.3 μg g −1 in the untreated oil to 14.8 μg kg −1, 9.9 μg kg −1, and 7.8 μg kg −1 in oils treated with Sepiolite, activated Bentonite, and industrial clay, respectively. Oxidative stability is enhanced in all ultrasonically‐treated oils by a significant ( p  < 0.05) reduction in Peroxide Value (PV) with the highest reduction (97%) observed in the presence of industrial clay (PV = 0.11 mEq kg −1 ). A corresponding reduction in Conjugated Dienes (CD) is also found in the treated samples ranging from 0.073–0.095% compared to 0.102% for the control. During accelerated storage at 60 °C, increase in PVs and CDs are significantly ( p  < 0.05) slower for the ultrasonically treated oils in the presence of clays compared to the control. Accelerated storage at 40 °C shows that the PV is greater in hempseed oil bleached with Sepiolite clay compared to a combination of Sepiolite and ultrasonic bleaching. Based on these results it is evident that the rapid removal of chlorophyll from cold pressed hempseed oil is enhanced by a combination of bleaching clay and ultrasonic treatment. Practical Applications : Ultrasonic treatment of cold pressed hempseed oil combined with bleaching clays proves very effective in reducing chlorophyll content. The method is not only rapid and clean but requires significantly less bleaching clay. Hempseed oil treated in this way exhibits greater oxidative stability making it more attractive for industrial and consumer use. The results of ultrasonic bleaching suggest its potential for prolonging the shelf‐life. Utilizing the ultrasonic bleaching technique as an alternative to conventional bleaching would be beneficial to the edible oil industry. The results of ultrasonic bleaching prove effectiveness in reducing chlorophyll content in cold‐pressed hempseed oil and suggest its potential for prolonging the shelf‐life. Abstract : The results of ultrasonic bleaching prove effectiveness in reducing chlorophyll content in cold‐pressed hempseed oil and suggest its potential for prolonging the shelf‐life.